Strategi Komunikasi Akun Instagram @Farizas_Kyas Dalam Mempromosikan Produk Busana Muslim Di Kalangan Remaja - Jihan Hanif Muarifah; Muhammad N. Abdurrazaq; Imang Maulana (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
The dynamics of contemporary development are correlated with integrated technological progress innovations in human activity, both in aspects of education, business, communication, and so on. The communication strategy is the choice of Instagram owner @Farizas_kyas as a marketing promotion for Muslim fashion products towards teenagers. Because, today's teenagers have followed trends as a reflection of modernity while remaining within the corridors of sharia principles. This research aims to examine and describe the communication strategy for promoting Muslim fashion products among teenagers by the Instagram account @Farizas_kyas. The research method uses a description method with a qualitative approach. The research subject is Farizas Kyas, while the research objects are material objects and formal objects. The data source was obtained from the Instagram account @Farizas_kyas through product posts and stories. Data collection was carried out through virtual observation, interviews and documentation. The research results confirm that the communication strategy for the Instagram account @Farizas_kyas in promoting Muslim fashion products among teenagers is done by creating attractive visual content, using hashtags, educational and informative content, live Instagram, and being consistent in posting content. By using an Instagram account, the account owner gets more benefits through the effectiveness of the product marketing strategy used.